In a Tradition of Learned Ministry: Wesley's ‘Foxe’ - Greenberg, Devorah (The journal of ecclesiastical history, 2008)
This examination of John Wesley's emendation and elaboration of John Foxe's Acts and monuments, shows how Wesley constructed Foxe's text and himself within a tradition of learned English ministry. Offering an expanded vision of the role and function of the popularly styled Book of Martyrs, this article combines readings of Wesley's journals and secondary analyses to permit insights into Wesley's relationship with the established Church of England, his intentions in taking up Foxe's text and his conceptions of hierarchy, pastoral duty and ministry. It contradicts scholarly expectation of anti-Catholic impulses behind Foxeian publications and their effects, and encourages a more nuanced appreciation of the contemporary application of the terms ‘Catholic’ and ‘papist’.